If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+1+13=26
We move all terms to the left:
3x+1+13-(26)=0
We add all the numbers together, and all the variables
3x-12=0
We move all terms containing x to the left, all other terms to the right
3x=12
x=12/3
x=4
| 3x+8=4x+10+8x | | 4xx=-3 | | x+7x4=16 | | -16t^2-29t+491=122 | | 8x+3x+8=4x+10 | | 7-2x=-15/8(-2x-2/3) | | 2x-5x÷6.3=-14.4 | | 6z=28+13z | | -16t^2-29+491=122 | | x+-6=1.5 | | -7b+5=7b+5 | | 6*3x-2=3*x | | 3x+2(x-1)=3x | | 3(2x-2)-17+3x=2(7x+1)-5x-9 | | 13+6x=7+5x | | 3(4-2m)=-13-11m | | 6.3x-2=3.x | | 5-2(x-3)+3(2x+4-x)=0 | | -2x-3+5x-3=-6 | | 3(x-2)=-8x+49 | | 7/9+p=3P=1/9 | | -7x-20=22 | | 8+2(x-4)=3x+4(2-x) | | 2(n+3)+2=12 | | 5v-15=-7(v+9) | | 9-6x-2-2x=10 | | x3=4096 | | 10n+5=15n-20 | | 10n+5=15n20 | | 14=6n+6−2n | | 5x+2=5x+272 | | -2(y+1)=-8y+46 |